The Internet and Civil Society: Environmental and Labour Organizations in Hong Kong - CHU, Yin-Wah (Institutional Knowledge at Singapore Management University, 2005)
To what extent has the Internet strengthened civil society? In which ways have civil society organizations (CSOs) used the internet to communicate their missions, enhance the discussion of public issues, extend networks and mobilize collective actions? This article seeks to answer these and related questions by reporting on an empirical study in Hong Kong. The study involves an analysis of the web pages launched by 14 environmental groups and 22 labour organizations on the one hand, and in-depth interviews with representatives of five of these organizations on the other. Due to the lack of resources and low level of e-readiness among most CSOs, as well as the prevalence of a parochial outlook among most labour organizations, the new technology has only found limited application in Hong Kong. At the same time, due to a top-down management orientation, the leaders of these CSOs have been more inclined to use the technology to communicate with each other than to build networks with rank-and-file members and supporters. Nonetheless, the findings of this study suggest that the technology has much potential for pluralizing public discourse, involving more people in rational-critical discussion of key public issues, as well as enhancing the capacity of existing CSOs to develop a sense of community and get mobilized. The technology also facilitates the emergence of novel types of collective action and as such taps into resources that are otherwise unavailable. In addition, the new technology makes it possible for individual activists to seek each other out, further cultivate their sense of community and launch collective actions on issues ignored by existing CSOs. Finally, it is through the synergy of online/offline discourses and activities that the internet exerts much of its positive impact on the expansion of civil society.